Impact of Dentofacial Deformity on Quality of Life: Age and Gender Differences Evaluated Through OQLQ, OHIP and SF36 - Marcelo Carlos Bortoluzzi; Priscila de Camargo Smolarek; Marcela Claudino; Eduardo B. Campagnoli; Rafael Manfro (Stilus Optimus, 2015)
Objectives: The aim of this study was to verify the impact of dentofacial deformity on quality of life and explore gender and age differences. Material and Methods: The impact of dentofacial deformity (DD) on quality of life was evaluated through questionnaires; Short Form Health Survey (SF36), Oral Health Impact Profile Questionnaire (OHIP), Orthognathic Quality of Life Questionnaire (OQLQ) and a single question answered by a Visual Analogue Scale. Results: Significant differences between male and female patients were observed in domains of OQLQ (oral function, P = 0.006; awareness of facial deformity, P = 0.018; and facial aesthetics, P < 0.001) and OHIP (physical pain, P = 0.006; psychological discomfort, P = 0.007; psychological disability, P = 0.006; and handicap, P = 0.01). Conclusions: The impact of dentofacial deformity was more pronounced in female Brazilian population. Age of patients with dentofacial deformity produced impacts over quality of life in different ways and according to the applied questionnaire and the interaction between age and gender may also produce different impacts in patients with dentofacial deformity. The domains of Orthognathic Quality of Life Questionnaire, Oral Health Impact Profile Questionnaire and Short Form Health Survey showed unaccepted distances in the pattern of answer rising doubts of their ability to assess quality of life as a generic and broad concept. There is a necessity to create a single quality of life instrument capable to measure impacts with sensitivity and specificity and from a generic concept to condition-specific health problem.